Behaviour of Stock Returns During COVID-19 Pandemic: Evidence from Six Selected Stock Market in the World - Malini, Helma (Jurnal Ekonomi Indonesia, 2020)
This paper investigates the short term return behavior of six selected stock market around the world during the COVID-19 Pandemic. USA, Indonesia, India, South Korea, Saudi Arabia, and Singapore are selected based on the size of their stock market and the countries have taken a considerable amount of decision and policy to mitigate the risk of before, ongoing, and aftermath COVID-19 Pandemic. This study relies on two major time series investigation techniques, namely Econometric Modeling of returns; The Autoregressive model, Assumption of Linearity, Volatility Modeling, namely the GARCH and WBAVR Test. The results suggest that the stock return behavior in six selected countries occurs in different forms. Our findings suggest that the policymakers must understand how to shift their policy to mitigate the risk of COVID-19 in the financial sector, since we observe a strong correlation between the public health crisis and stock market performances.